A dinâmica do crédito na economia brasileira: um ensaio. - Melo, Marcelo Miranda de (2009)
This academic research analyzed the credit dynamics, as an important channel for monetary policy transitions in the Brazilian economy. In the first chapter, credit aggregate series for families, companies, private sector and public sector were selected. In the second chapter were selected rural credit series such as: agriculture, cattle, rural investment, rural trading and rural costing. In the third chapter, the increase rate of the relation Credit\GDP was used as proxy of the aggregate liquidity as well as sectoral GDPs. The methodology applied was VAR\VEC econometric models, Granger causality test, Impulse Response Function and Cholesky`s Variance Decomposition. The credit impact in the aggregate GDP as well as in the sectoral GDPs, depend on the credit type and the persistence of its shocks.